PERANAN BADAN USAHA MILIK DESA (BUMDes) LANCANG KUNING DALAM PENINGKATAN EKONOMI MASYARAKAT PENGGUNA DANA BUMDes DESA RUMBAI JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Yeni Afiza (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
BUMDes is a village enterprise managed by the community and village government in an effort to strengthen the village economy and is shaped based on village needs and potentials. BUMDes is a pillar of the village economy that functions as a social and commercial institution that stands in the interest of the community and seeks profit. This study aims to determine the role of Village Owned Enterprises (BUMDes) Lancang Kuning to improving the economic community in Rumbai Jaya Village Kempas Sub-district Indragiri Hilir Regency. The methode of research is qualitative discriptive, only describing the resulth of i nterview. The resulth of research showed the BUMDes Lancang Kuning have role to improve economic of user of BUMDes. It show by parameters : (1) increase of business ( 76,20% respondent ), (2) increase of income (76,20% respondent ), (3) increase of household properties (57,10% respondent).